(untitled) (International Journal of Engineering and Computer Science, 2014)
All database systems must be able to respond to requests for information from the user that is process queries. Secure and efficient algorithms are needed that provide the ability to query over encrypted database and allow optimized encryption and decryption of data. Data encryption is a strong option for security of data in database and especially in those organizations where security risks are high. Firms outsourcing their databases to untrusted parties started to look for new ways to securely store data and efficiently query them. When we apply encryption on database then we should compromise between the security and efficient query processing, because the operations of encryption and decryption greatly degrade query performance. This paper presents a survey on various encryption algorithms and identifies many of the common issues, themes, and approaches that cover query processing. Also in this paper a survey is made based on performance of query processing as well as pros and cons of existing algorithms.